(untitled) (International Journal of Language, Literacy and Translation, 2025)
This paper examines strategies to improve reading skills among Grade Four learners in rural primary schools within the O.R. Tambo Coastal District, Eastern Cape, South Africa. The study sought to identify practical approaches for improving reading proficiency in this context. It was grounded in Lev Vygotsky’s social constructivism theory, which emphasises the importance of social interaction in learning; in this case, the emphasis is put on grades. An interpretive paradigm guided the research process. The study adopted a qualitative methodology with a case study design, and data were gathered through semi-structured interviews conducted with ten Grade Four teachers selected through convenience sampling. Thematic analysis was used to analyse the data. Key findings revealed effective strategies to enhance reading skills, including the use of picture books, the "Drop Everything and Read" initiative, grouping learners according to ability, and employing diverse teaching methods and styles. These strategies were designed to cater to the diverse needs of learners and promote engagement with reading. The study addresses a significant gap, as limited research and implementation efforts have been made in rural primary schools regarding reading enhancement strategies. The recommendations propose that educational stakeholders collaborate to cultivate a strong reading culture through targeted interventions. These include organising workshops focused solely on reading instruction strategies and fostering more significant support for teachers in rural settings. By implementing these recommendations, Grade Four learners stand to benefit from improved reading skills, laying out a stronger foundation for academic success in their learning. This research makes a meaningful contribution to the discourse on literacy development in under-resourced educational contexts.